Business support and training in minority-ethnic, family-run firms: the case of SMEs in Scotland. Issue 5 (20th October 2019) - Cunningham, James; McGuire, David
ABSTRACT: Minority-ethnic, family-run SMEs perform an increasingly important role in the Scottish economy. Yet, research has identified that such businesses are less likely to access publicly funded business support and training opportunities. This paper draws upon 14 interviews with senior representatives of minority-ethnic, family-run SMEs as well as government agencies and business support organizations to assess the perceived barriers to accessing such support and reports upon the internal dynamics within such businesses. The findings show that minority-ethnic, family-run firms are nested in particular value systems and narratives that exist to protect both the family unit and business entity and give voice to their history and experience. Such firms exhibit a high level of internal control and self-reliance with a preference for individual trust-based relationships rather than formal arrangements with public institutions. The findings also show a disconnect between universalistic business support provision available from government agencies and the preference by minority-ethnic, family-run SMEs for more specific solutions. The paper concludes that family and ethnic cultures play an important role in how minority-ethnic, family-run SMEs choose to learn and this makes the provision of business support and training a complex and often paradoxical issue.